2017
DOI: 10.1002/pds.4254
|View full text |Cite
|
Sign up to set email alerts
|

Using prescription monitoring program data to characterize out‐of‐pocket payments for opioid prescriptions in a state Medicaid program

Abstract: Prescription opioid fills that were likely paid out-of-pocket were common and associated with several known indicators of high-risk opioid use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…While this research noted decreases in opioid utilization, these decreases may reflect only those prescriptions that were submitted to Medicaid for payment and may not reflect final receipt of prescriptions to the patients themselves. Recent studies suggest that cash payment for opioids is not uncommon . Finally, buprenorphine prescriptions in our analysis could potentially be used for pain, medication‐assisted treatment (MAT) or both.…”
Section: Discussionmentioning
confidence: 99%
“…While this research noted decreases in opioid utilization, these decreases may reflect only those prescriptions that were submitted to Medicaid for payment and may not reflect final receipt of prescriptions to the patients themselves. Recent studies suggest that cash payment for opioids is not uncommon . Finally, buprenorphine prescriptions in our analysis could potentially be used for pain, medication‐assisted treatment (MAT) or both.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we likely underestimated the opioid prescription rate if some patients filled prescriptions by paying out of pocket instead of using health insurance. 28 Finally, if data from 2017 were available and used to replicate this analysis, there may be a lower measured association with prolonged use to due to the increase in prescription drug monitoring programs (PDMPs), 29,30 prescribing guidelines, 31 and the explosion in the availability and use of low-cost illicit opioids. 32,33 All these factors increase the likelihood of an earlier transition to illicit opioids rather than seeking repeated prescription fills for individuals developing a new opioid use disorder after exposure to a prescription opioid.…”
Section: Limitationsmentioning
confidence: 99%
“…Medicaid data were linked to the Oregon PDMP by an analyst at OHA using a probabilistic linkage on name, date of birth, and ZIP code using LinkKing (v7.1) software. Details of the Medicaid‐PDMP linkage have been previously described 21,22 . We then summarized opioid fills and claims characteristics by month.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Roberts et al found an increased likelihood of paying out‐of‐pocket for controlled substances after referral to a lock‐in program in North Carolina's Medicaid program 9,20 . Prior studies in Oregon estimated that 13.5% of dispensed opioids among Medicaid beneficiaries were potentially paid out‐of‐pocket; however, these estimates used data prior to OHA's opioid initiative (2012‐2013) 21 . Therefore, we expect trends in potential cash‐pay opioid fills, particularly in the period of the OHA Opioid Initiative, to increase.…”
Section: Introductionmentioning
confidence: 99%